(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The author argues that the ‘New’ Israeli Nationality Law is, despite its name, a natural, almost inevitable, product of the Zionist project in Palestine. Besides representing Zionist ideology, the law is part of a long-term attempt by the Israeli government to adjust Zionism to present-day realities and solve the so-called ‘demographic problem’ of the Jewish State.